Microvascular cerebral blood flow response to intrathecal nicardipine is associated with delayed cerebral ischemia - Sathialingam, Eashani; Cowdrick, Kyle R.; Liew, Amanda Y.; Fang, Zhou; Lee, Seung Yup; McCracken, Courtney E.; Akbik, Feras; Samuels, Owen B.; Kandiah, Prem; Sadan, Ofer; Buckley, Erin M. (Frontiers in Neurology, 2023)
One of the common complications of non-traumatic subarachnoid hemorrhage (SAH) is delayed cerebral ischemia (DCI). Intrathecal (IT) administration of nicardipine, a calcium channel blocker (CCB), upon detection of large-artery cerebral vasospasm holds promise as a treatment that reduces the incidence of DCI. In this observational study, we prospectively employed a non-invasive optical modality called diffuse correlation spectroscopy (DCS) to quantify the acute microvascular cerebral blood flow (CBF) response to IT nicardipine (up to 90 min) in 20 patients with medium-high grade non-traumatic SAH. On average, CBF increased significantly with time post-administration. However, the CBF response was heterogeneous across subjects. A latent class mixture model was able to classify 19 out of 20 patients into two distinct classes of CBF response: patients in Class 1 (n = 6) showed no significant change in CBF, while patients in Class 2 (n = 13) showed a pronounced increase in CBF in response to nicardipine. The incidence of DCI was 5 out of 6 in Class 1 and 1 out of 13 in Class 2 (p < 0.001). These results suggest that the acute (<90 min) DCS-measured CBF response to IT nicardipine is associated with intermediate-term (up to 3 weeks) development of DCI.